2018
DOI: 10.1002/app.46645
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan hydrogel‐coated cotton fabric: Antibacterial, pH‐responsiveness, and physical properties

Abstract: In this work, chitosan hydrogel has been synthesized and used to impart pH‐sensitivity and antimicrobial finish to cotton fabric. In order to enhance the incorporation rate of hydrogel, anionic, and cationic activation of the textile surface was applied and then compared. The antibacterial activity of the fabric was then studied. The results revealed an enhancement of the antibacterial activities of the modified fabrics against Escherichia coli, Listeria monocytogene, and Staphylococcus aureus bacteria's. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Such an approach has also been adapted in a previous study on the effect of demineralization on degradable chitosan fiber. 9 Other articles involve bio-performances, such as cell growth 10 and emission 11 promotion, acid resistance, 12,13 and chemical extraction. 14,15 Articles involving the anti-microbial performance of chitosan mostly focus on the solution state, and therefore in this study we conducted chitosan anti-microbial performance tests in both its fiber and solution states.…”
Section: Experiments Methodsmentioning
confidence: 99%
“…Such an approach has also been adapted in a previous study on the effect of demineralization on degradable chitosan fiber. 9 Other articles involve bio-performances, such as cell growth 10 and emission 11 promotion, acid resistance, 12,13 and chemical extraction. 14,15 Articles involving the anti-microbial performance of chitosan mostly focus on the solution state, and therefore in this study we conducted chitosan anti-microbial performance tests in both its fiber and solution states.…”
Section: Experiments Methodsmentioning
confidence: 99%
“…15 Woven glass fabric–reinforced and high energy-dissipative polyampholyte matrix hydrogel composite as strong structural biomaterial with high toughness and tensile properties were produced by Huang et al 13 Cotton (Co) fabric was treated with as-synthesized chitosan hydrogel for pH sensitivity and antimicrobial properties. 16 The surface of fabric was modified with hydrogel via covalent bonding for wound dressing application that the hydrogel structure was isolated from protein. 17 Konjac glucomannan–based hydrogel was prepared and coated on glass fabrics for oil–water separation in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…The load-to-failure capacity of neat textiles via hydrogel infiltration and wear resistance of the hydrogel matrix were improved. Recent studies were reported in the literature on hydrogel coated or treated fabric structures, but one-step preparation of fabric-reinforced hydrogel structures from a woven fabric has not been studied [1618].…”
Section: Introductionmentioning
confidence: 99%